Hubungan antara Work Engagement dengan Komitmen Organisasi pada Karyawan Super Dazzle di Daerah Istimewa Yogyakarta - Bella Azahar Br Tarigan; Arundati Shinta; Femmy Lekahena (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Employee commitment to the organization is an important aspect that must be possessed in supporting the sustainability and achievement of company goals. The purpose of this study is to empirically prove the relationship between work engagement and organizational commitment among Super Dazzle employees in the Special Region of Yogyakarta. A total of 115 of the total 198 Super Dazzle DIY employees were selected as samples using the Proportional Simple Random Sampling technique. The measuring instrument used in this study consisted of two scales, namely the Organizational Commitment scale and the Work Engagement scale. The results of the study found a correlation coefficient value of 0.657 (p <0.000). This value indicates a significant positive relationship between work engagement and organizational commitment among Super Dazzle employees in DIY.